Education On Clean And Healthy Living BehaviorAmong Students At Muhammadiyah 4 Junior High School Margahayu, Bandung Regency - Hendra Gunawan; Iyep Dede Supriyatna; Rima Melati; Nita Rismawati (Jurnal Sentra Pengabdian, 2025)
Clean and healthy living behavior is a set of practices that individuals must adopt in order to maintain, preserve, and improve their health status. Schools are one of the environments that can serve as a platform for the socialization and habituation of clean and healthy living behaviors. Schools are strategic places for cultivating such behaviors. This activity aims to enhance students' knowledge, understanding, and awareness of the importance of clean and healthy living behavior within the school setting. The implementation method of the activity consists of four stages: obtaining permission, program socialization, activity execution, evaluation, and follow-up. The participants in this community service activity were 38 students from SMP Muhammadiyah 4 Margahayu, Bandung Regency. The results of the activity showed an improvement in students' knowledge, with the average pre-test score being 70.21 and increasing to 77.63 in the post-test. The conclusion of this community service activity is that the students responded positively, as indicated by the interactive discussion that took place with the speaker.